Design and Mathematical Analysis of a Novel Reluctance Force-Type Hybrid Magnetic Bearing for Flywheel with Gimballing Capability. (20th May 2013) - Wang, Chun'e; Tang, Jiqiang
Abstract : Magnetically suspended flywheel (MSFW) with gimballing capability fulfills requirements of precision and maneuvers for space applications. A novel reluctance force-type hybrid magnetic bearing (RFHMB) is presented based on analysis of demerits of Lorentz force-type magnetic bearing and common RFHMB. It features that radial and axial magnetic bearing units are integrated into a compact assembly with four separate biased permanent magnets and two conical stators; four radial poles with shoes and rotor made of iron-based amorphousness can reduce eddy loss. Equivalent magnetic circuits of permanent magnets and their control currents are presented. Simulation results indicate flux density fluctuates from 0.272 T to 0.41 T; rotor tilting does not affect the suspension force when rotor only tilts around X -axis or Y -axis. When rotor drifts in X, Y, or Z direction and tilts around X -axis or Y -axis simultaneously, force in corresponding directions slightly increases with tilting angle's enlargement, but the maximum change does not exceed 14%. Additional tilting torque mainly determined by uniformity of flux density in conical air gaps is 0.05 Nm which is far smaller than 11 Nm in common RFHMB; magnetic suspension force is effectively decoupled among X, Y, and Z directions; results prove that MSFW with gimballing capability theoretically meets maneuvering requirement of spacecraft.